Does Mandatory Labeling of Genetically Modified Food Grant Consumers the Right to Know? Evidence from an Economic Experiment - Astrid Dannenberg; Sara Scatasta; Bodo Sturm (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Opponents of the voluntary labeling scheme for genetically modified (GM) food products often argue that consumers have the ?right to know? and therefore advocate mandatory labeling. In this paper we argue against this line of reasoning. Using experimental auctions conducted with a sample of the resident population of Mannheim, Germany, we show that the quality of the informational signal generated by a mandatory labeling scheme is affected by the number of labels in the market. If there are two labels, one for GM products and one for non-GM products, mandatory and voluntary labeling schemes generate a similar degree of uncertainty about the quality of products that do not carry a label.
Keywords: Q51; C91; Q18; 330; labeling; genetically modified foods; consumer preferences; experimental auctions